The importance of studying consumer behavior in supporting local food production - Steliana Rodino; Ion Toncea; Ruxandra Pop (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
This study objective was to highlight the importance of studying consumer behavior and set up a methodological framework for such a study with applicability in encouraging the production of protein plants in order to diversify local production. Understanding consumer behavior is an important step for building strategies towards promoting local food production. Consumer behavior insights may be able to help in creating targeted marketing strategies that emphasize the benefits of local products, such as freshness, quality, and community support, thereby fostering a responsible consumption model and ensuring food security. The importance of studying consumer behavior in supporting local food production has a threefold importance: for promoting a responsible consumption model, for supporting local economies and reducing the environmental impact associated with transporting food over long distances.
Keywords: D11; M31; O33; 330; vegetal protein; local production; sustainable consumption; consumer's expectations; methodological framework